Cell and tissue responses at the interface with a chitosan hydrogel intended for vascular applications: in vitro and in vivo exploration. (31st January 2019) - Aussel, Audrey; Boiziau, Claudine; L'Azou, Béatrice; Siadous, Robin; Delmond, Samantha; Montembault, Alexandra; David, Laurent; Bordenave, Laurence; Thébaud, Noëlie-Brunehilde
Abstract: Aims . The need for small caliber vessels to treat cardiovascular diseases has grown. However, synthetic polymers perform poorly in small-diameter applications. Chitosan hydrogels can provide a novel biological scaffold for vascular engineering. The goal of this study was to explore host cell and tissue behavior at the interface with chitosan-based scaffolds in vitro and in vivo . Methods and results. in vitro, we assessed the ability of endothelial cells lining chitosan hydrogels to produce tissue factor (TF), thrombomodulin (TM) and nitric oxide. We showed that endothelial cells behave as a native endothelium since under stimulation, TF and TM expression increased and decreased, respectively. Endothelial cells seeded on chitosan produced nitric oxide, but no change was observed under stimulation. After in vivo subcutaneous implantation of chitosan hydrogels in rats, macrophage activation phenotypes, playing a crucial role in biomaterial/tissue, were explored by immunohistochemistry. Our results suggested a balance between pro- and anti-inflammatory signals since we observed an inflammatory response in favor of macrophage M2 phenotype. Conclusion . in vitro exploration of endothelial cell response at the interface with chitosan hydrogel showed a functional endothelium and in vivo exploration of tissue response revealed a biointegration of chitosan hydrogels.